Arquitetura Bancária: sede de um banco digital em Palmas - TO e11even bank - Teixeira, Mateus Eduardo Mathias (Universidade Federal do Tocantins, 2021)
Considering how fintechs are revolutionizing the global financial market, this Conclusion Work aims to elaborate a project for the headquarters of a digital bank in the city of Palmas, in the state of Tocantins, based on sustainable principles and differentiating it from a traditional bank branch.